2009
DOI: 10.1145/1543135.1542520
|View full text |Cite
|
Sign up to set email alerts
|

A study of memory management for web-based applications on multicore processors

Abstract: More and more server workloads are becoming Web-based. In these Web-based workloads, most of the memory objects are used only during one transaction. We study the effect of the memory management approaches on the performance of such Web-based applications on two modern multicore processors. In particular, using six PHP applications, we compare a general-purpose allocator (the default allocator of the PHP runtime) and a region-based allocator, which can reduce the cost of memory management by not supporting per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This is the case for web-based applications where memory objects belong to transactions. Inoue et al have shown that allocators which tend to perform coalescing on each case of freeing an object behave poorly in multicore environments [18]. The allocation technique that they suggested eliminates coalescing, which in turn reduces bus tra c in multicore processors; it makes 11.4% to 51.5% performance improvement compared to default allocators which do perform coalescing [18].…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for web-based applications where memory objects belong to transactions. Inoue et al have shown that allocators which tend to perform coalescing on each case of freeing an object behave poorly in multicore environments [18]. The allocation technique that they suggested eliminates coalescing, which in turn reduces bus tra c in multicore processors; it makes 11.4% to 51.5% performance improvement compared to default allocators which do perform coalescing [18].…”
Section: Discussionmentioning
confidence: 99%